RESERVATION SYSTEM ON THE GARMENT KNITTED CLOTHES ALDY'S BY USING MICROSOFT VISUAL BASIC 6.0 - Hendi Irawan; Drs. Sutarno Usna, MMSI (Jurnal Sistem Informasi, 2005)
Systems sales of goods that are running currently on companies often have difficulty in doing data collection of goods sold, and the results of the calculation of bookings and sales of the bookings made for the report. For that need to be made at the company's computerized system, where incoming data will be easily processed with accuracy and speed. Checks will also produce more accurate results and calculation of bookings will be stored properly.